ANALISIS PERMASALAHAN SOSIAL DALAM NOVEL RUMAH TANPA JENDELA KARYA ASMA NADIA - Anugrah, Ade Mesti; Effendy, Chairil; Priyadi, A Totok (Universitas Tanjungpura, 2023)
This study aims to increase the reader's understanding of social problems and their causes in the novel Rumah Tanpa Jendela by Asma Nadia. The theory used in this research is the sociology of literature. This study uses a descriptive method in the form of qualitative research. The data source in this research is the novel Rumah Tanpa Jendela by Asma Nadia. The data in this study are quotes, words, phrases and sentences that describe social problems and their causal factors. The data collection technique in this research is content analysis. The results of this study showed that the social problems contained in the novel Rumah Tanpa Jendela are population problems(residential problems and population density, employment problems, education problems, and health problems), poverty problems, violence problems, crime problems, and family organization. The contributing factors are economic factors, biological factors, psychological factors, government policy factors, and disaster factors. The implementation plan for learning the results of this research is thepreparation of lesson plans based on Indonesian language learning for class XII high school curriculum 2013. The competencies used are KD 3.1 understanding the structure and linguistic rules of novel texts both oral and written and KD 4.1 interpreting the meaning of novel texts both oral and written. The novel Rumah Tanpa Jendela by Asma Nadia has become an Indonesian language learning material.